Bread consumption patterns in a Swedish national dietary survey focusing particularly on whole-grain and rye bread - Pernilla Sandvik; Iwona Kihlberg; Anna Karin Lindroos; Ingela Marklinder; Margaretha Nydahl (Food & Nutrition Research, 2014)
Background: Bread types with high contents of whole grains and rye are associated with beneficial health effects. Consumer characteristics of different bread consumption patterns are however not well known. Objective: To compare bread consumption patterns among Swedish adults in relation to selected socio-demographic, geographic, and lifestyle-related factors. For selected consumer groups, the further aim is to investigate the intake of whole grains and the context of bread consumption, that is, where and when it is consumed. Design: Secondary analysis was performed on bread consumption data from a national dietary survey (n=1,435). Respondents were segmented into consumer groups according to the type and amount of bread consumed. Multiple logistic regressions were performed to study how selected socio-demographic, geographic, and lifestyle-related factors were associated with the consumer groups. Selected consumption groups were compared in terms of whole-grain intake and consumption context. Consumption in different age groups was analysed more in detail. Results: One-third of the respondents consumed mainly white bread. Socio-demographic, geographic, and healthy-lifestyle-related factors were associated with the bread type consumed. White bread consumption was associated with younger age groups, less education, children in the family, eating less fruit and vegetables, and more candy and snacks; the opposite was seen for mainly whole-grain bread consumers. Older age groups more often reported eating dry crisp bread, whole-grain bread, and whole-grain rye bread with sourdough whereas younger respondents reported eating bread outside the home, something that also mainly white bread eaters did. Low consumers of bread also consumed less whole grain in total. Conclusions: Traditional bread consumption structures were observed, as was a transition among young consumers who more often consumed fast food bread and bread outside the home, as well as less rye and whole-grain bread. Target groups for communication strategies and product development of more sensorily attractive rye or whole-grain-rich bread should be younger age groups (18–30 years), families with children, and groups with lower educational levels.